A topological optimization algorithm applied to the design of composites patch repair of mixed-mode cracked plate - Braun, Matias Nicolas (2017)
In this work, a topology optimization algorithm is developed and implemented to get an optimum composite patch shape. Typically, the design process consists of an iterative analysis, where the best solution is obtained from a comparative study. In this way, we propose a topology optimization algorithm applied to obtain the optimum composite patch shape. The algorithm is implemented in MatLab, and uses the commercial finite element code Abaqus/Standard. A numerical example is analysed to show the capability of the proposed method. The obtained results are compared with numerical results reported by other researchers, revealing the potential of the developed algorithm.